Horned Armadillos and Rafting Monkeys : The Fascinating Fossil Mammals of South America - Croft, Darin A. (Book collections on Project MUSE., 2016)
South America is home to some of the most distinctive mammals on Earth'giant armadillos, tiny anteaters, the world's largest rodent, and its smallest deer. But the continent once supported a variety of other equally intriguing mammals that have no close living relatives: armored mammals with tail clubs, saber-toothed marsupials, and even a swimming sloth. We know of the existence of these peculiar species thanks to South America's rich fossil record, which provides many glimpses of prehistoric mammals and the ecosystems in which they lived. Organized as a "walk through time" and featuring species from 15 important fossil sites, this book is the most extensive and richly illustrated volume devoted exclusively to the Cenozoic mammals of South America. The text is supported by 75 life reconstructions of extinct species in their native habitats, as well as photographs of fossil specimens and the sites highlighted in the book. An annotated bibliography is included for those interested in delving into the scientific literature.